Improving Digital Literacy in Pekijing Village, Serang City: The Participatory Rural Appraisal Approach - Yulianti, Rachmi; Palupi, Icha (Indonesian Journal of Social Science Research, 2025)
This study aims to examine the local government's strategy in improving digital literacy in Pekijing Village, Serang City, using the Participatory Rural Appraisal (PRA) approach. Low digital literacy limits access to information, digital public services, and digital economic opportunities. The method used is descriptive qualitative with observation, interview, and documentation techniques. The results show that government strategies are still sectoral in nature, uncoordinated, and lack technical regulations at the local village level. However, community participation in Pekijing Village is actually quite high, as reflected in the existence of reading parks, reading room bookshelves, and the enthusiasm of residents to learn. This study recommends strengthening regulations, cross-sector collaboration, and a participatory approach in building an inclusive and sustainable digital literacy ecosystem.